Energy transport analysis in natural convective flow of water:Ethylene glycol (50:50)-based nanofluid around a spinning down-pointing vertical cone - Iqbal, Zahoor; Yashodha, S.; Hakeem, A. K. Abdul; Alsawi, Abdulrahman; Alyami, Maryam Ahmed; Yousef, El. Sayed; Amin, Ali H.; Eldin, Sayed M. (Frontiers in Materials, 2022)
The influence of the magnetic field on H2O−C2H6O2 (50:50)-based nanofluid over a heated and spinning vertical cone is deliberated. Water: ethylene glycol (50:50) mixture-based nanofluid with Al2O3 and Fe3O4 as nanoparticles exhibits higher thermal conductivity enhancement. Heat transfer analysis for the spinning vertical cone with a prescribed surface temperature was investigated. The influence of magnetic parameter, spin parameter, and nanoparticle volume fraction on tangential velocity profile, spin velocity profile, and thermal profile is analyzed. The results accord strongly with the findings of previous research works in the special cases. Computation shows that as magnetic parameter increases, the thicknesses of hydrodynamic and thermal boundary layers decrease and increase, respectively. The addition of nanoparticles (Al2O3 and Fe3O4) effectively enhances the skin friction coefficient and Nusselt number.